2013
DOI: 10.1111/anu.12035
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and production of three species of purple non-sulphur bacteria grown in palm oil mill effluent and their application in rotifer culture

Abstract: Three species of purple non‐sulphur bacteria (PB), Rhodopseudomonas palustris, Rhodobacter sphaeroides and Rhodovulum sulfidophilum, grown in palm oil mill effluent (POME) were successfully used for the first time as feed for rotifers (Brachionus rotundiformis). Rp. palustris cultured in both POME and synthetic medium gave the highest rotifer density (332–395 individuals mL−1) from 3 to 5 days at 10 g L−1 salinity. Other PB cultured in synthetic medium generally support higher rotifer density than PB cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…data). On the other hand, 1 kg dry weight of microalgae could cost USD50.00 (Eirik, Augustin & Vernon ) or USD46.44 for Spirulina and Chlorella (Brennan & Owende ) while the equivalent dry weight of bPB would cost USD23.29 (Loo, Chong & Vikineswary ).…”
Section: Discussionmentioning
confidence: 99%
“…data). On the other hand, 1 kg dry weight of microalgae could cost USD50.00 (Eirik, Augustin & Vernon ) or USD46.44 for Spirulina and Chlorella (Brennan & Owende ) while the equivalent dry weight of bPB would cost USD23.29 (Loo, Chong & Vikineswary ).…”
Section: Discussionmentioning
confidence: 99%
“…In a different nutritional application, Loo et al . () produced non‐sulphur bacteria ( Rhodopseudomonas palustris , Rhodobacter sphaeroides and Rhodovulum sulfidophilum ) in palm oil mill effluent and applied the bacterial biomass to culture rotifers. Rotifers fed R. sulfidophilum grown in palm oil mill effluent had significantly higher amounts of protein, arachidonic acid, EPA and DHA than rotifers fed bacteria grown in conventional synthetic medium.…”
Section: Emerging and Current Microbial Production Methodsmentioning
confidence: 99%
“…Moreover, it has been reported that the nutritional content of bacteria and microalgae can be significantly modified by applying specific culture media and growth conditions (Loo et al . ; Huang & Su ).The cell walls of yeast comprise from 25 to 32% of the cell weight (Ferreira et al . ).…”
Section: Nutritional Value Of Microorganisms and Their Cellular Compomentioning
confidence: 99%
“…Furthermore, the nutritional content of bacteria can be considerably modified by applying a specific culture medium and optimum growth conditions (Loo et al . ; Huang & Su ). Additionally, some types of bacterial cell walls represent an important source of nutrients because cell walls are principally composed of protein (13%) and polysaccharides (85–88%) (Nguyen et al .…”
Section: Nutritional Values Of Bacterial Cellular Componentsmentioning
confidence: 99%